The Impact of Growth Temperature on Nanorod Morphology and Optical Properties for CH3NH3PbI3 Perovskite Solar Cell Device Application. (2019) - Mufti, Nandang; K R Laila, Ifa; Fuad, Abdulloh; Taufiq, Ahmad; Sunaryono
Abstract: Perovskite solar cells have been studied intensively by photovoltaic researchers in recent years due to their ability to absorb proper light. This research describes the CH3 NH3 PbI3 perovskite solar cell fabrication process. The solar cell structure is composed of ITO/ZnO seed layer/ZnO NRs/CH3 NH3 PbI3, with ZnO NRs as a nano shaped stem layer where perovskite crystals form. ZnO NRs have been successfully synthesized on the ITO substrate by a hydrothermal method. The ZnO seed layer is synthesized by a spin coating method in a mixture of zinc acetate dihydrate solution and ethanol. ZnO NRs were synthesized using hexamethylenetetramine (HMT) and zinc nitrate with a 1:1 molar ratio for 6 h. Some variations in growth temperature used were 80, 90 and 100 o C with a zinc nitrate concentration of 50 mM. Similarly, perovskite film devices are made through a two-step deposition using PbI2 and CH3 NH3 I as the main ingredients. The effects of synthesis conditions on ZnO NRs film and perovskite film devices were systematically investigated to look at the structure, morphology, optical properties of films and electrical properties of films using X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), IV meter and LCR AC meter. The SEM results show that as the temperature increases, the size of the diameter and length of the rods are increased. The large rod diameter and length decrease the value of energy band gap. ZnO NRs synthesized with 50 mM concentrations at 100 o C showed the best results regarding morphology and optical properties. The film has a diameter size of 365 nm, length of the rod of 5.1 µm, and an energy band gap of 3.15 eV. The diffraction results.